The position of Poland in the flows of foreign direct investments within the European Union in XXI century - Skulska, Bogusława (Publishing House of the Wrocław University of Economics, 2009)
The integration of Poland with the EU should facilitate its joining the globa-lisation stream and taking advantage of its positive sides. Fulfilling these aims, however, depends primarily on the country’s activity, including individual enter-prises, in making use of the opportunities offered to Poland by the EU. The membership in the Union creates above all a unique chance for a sustained social and economic growth. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 397-406